Ali Muhammad Ash-Shallabi's Thoughts About the Position of Women - Muhammad Sabri (LPPM IAIN Parepare, 2024)
This article aims to explore Ali Muhammad Ash-Shallabi’s thoughts on understanding the position of women in the domestic sphere, public sphere, and typology in understanding the postulates of women. The research method used is descriptive-analytical. It involves describing the construction of Muhammad Ash-Shallabi's thoughts and critically analyzing them to identify the roots of his thought construction. Additionally, it examines the strengths and weaknesses of other figures. The author's primary data is the